Analysis of the costs and benefits of building A1 highway - Rupčić, Nataša; Gašparović, Tomislav (Oeconomica Jadertina, 2019)
Decision-making in public companies does not take place solely based on profitability criteria, but it concerns the merging of market and public criteria. However, despite the diversity of objectives that public sector projects need to meet, and the fact that decisions are made through the process of political negotiation between stakeholders, the basis for making decisions ought to be an analysis of costs and benefits. Thus, it should include all benefits, both material and immaterial, direct and indirect. Yet, one should bear in mind that the project should be cost-effective, both in the construction phase and at the stage of use and maintenance. This paper analyses decisions made in the HAC (Croatian Highways) public company with an emphasis on management decisions when building the A1 motorway. During the construction of this highway, the objectives were to connect the state territory, connect with the European highway network, develop tourism and increase traffic safety. These objectives have been achieved. However, the desired goals of increasing development, specifically the economic development of rural and less-populated areas, and the retention and increase of the population have not been achieved. The project commercial goals have also not been realized. The costs of building Bosiljevo-Split highway section exceeded the planned costs by 3 billion Croatian kuna. The revenues from 2015 to 2017 were on average 500 million Croatian kuna less than projected. Based on these data, the question is whether the A1 motorway should have been built via a loan or through a public-private partnership. Given projection errors, it can be assumed that a model of public-private partnership would have implied a more realistic assessment of traffic dynamics, lower cost of construction, better revenue management, and probably more gradual construction.